KEKERABATAN BAHASA BATAK TOBA DENGAN BAHASA BATAK MANDAILING - Farida Meliana Hutabarat; Ermanto Ermanto; Novia Juita (Jurnal Bahasa dan Sastra, 2013)
This article is to (1) describe the persentage rate in relationship (2) betwenn Batak Toba and Batak Mandailing Languange, counting the time space when these two languanges were once separated, (3) to the describe the sound correspondence between Batak Toba and Batak Mandailing languange. This research’s data is two hundred Swadesh words added with twohundred cultural words as qualitatif proff. These four hundred words is also used as the instrument of this research. First, the amount of related words between Batak Toba and Batak Mandailing languange are 128 words and the paersentage rate between those two languange is 64%. Second, the time space between Batak Toba and Batak Mandailing languange is 1027 years ago, counting from now (2013). Third, the proofs/evidences of sound correspondence between Batak Toba and Batak Mandailing languange.